Non-invasive imaging of carotid arterial restenosis using 3T cardiovascular magnetic resonance. - Lindsay, A; Biasiolli, L; Knight, S; Cunnington, C; Robson, M; Neubauer, S; Kennedy, J; Handa, A; Choudhury, R (2014)
BACKGROUND: Restenosis of the carotid artery is common following carotid endarterectomy, but analysis of lesion composition has mostly been based on histological study of explanted restenotic lesions. This study investigated the ability of 3T cardiovascular magnetic resonance (CMR) to determine the components of recurrent carotid artery disease and examined whether these differed from primary atherosclerotic plaque. METHODS: 50 patients underwent 3T CMR of both carotid arteries using a standard multicontrast protocol: time-of-flight (TOF), T1-weighted (T1W), T2-weighted (T2W), and PD-weighted (PDW) Turbo-Spin-Echo (TSE) sequences. 25 patients had previously undergone carotid endarterectomy (mean time since surgery 1580 days, range 45-6560 days), and 25 with primary asymptomatic atherosclerotic plaques served as controls. Two experienced reviewers analysed the multicontrast CMR images according to the presence or absence of major plaque features and assigned an overall classification type. RESULTS: In patients with recurrent carotid disease following endarterectomy, the mean degree of restenosis was 51% (range 30-90%). Three distinct types of restenosis were identified: 5 patients (20%) showed CMR characteristics of fibro-atheromatous tissue, 11 patients (44%) had plaque features consistent with possible myointimal (fibromuscular) hyperplasia, and 6 patients (24%) had recurrent plaque suggestive of further lipid accumulation. Three patients (12%) showed evidence of post-surgical dissection of the carotid intima. Compared to primary atherosclerotic plaques, restenotic plaques were more likely to contain fibro-atheromatous tissue (p = 0.05) and smooth muscle (p < 0.01), and less likely to contain lipid (p < 0.01). Composition did not differ significantly between patients with early and late restenosis. CONCLUSIONS: As defined by CMR, restenotic lesions of the carotid artery fall into three distinct types and differ in composition from primary atherosclerotic plaques. If validated by subsequent histological studies, these findings could suggest a role for CMR in detecting high-risk (i.e. lipid-rich) restenotic lesions.